Analisis Efektifitas Struktur Pengendalian Internal Sistem Penerimaan Kas dan Persediaan Dagang pada PT NICOSA Sejahtera di Lampung Timur. - Dewantara, Andika; Suyanto, Suyanto; Nusantoro, Jawoto (Universitas Muhammadiyah Metro, 2023)
This research was conducted at PT. Nicosa Sejahtera, East Lampung. The aims of the study are to know and analysis the structure of the internal control system of cash receipts and inventory applied on PT. Nicosa Sejahtera, East Lampung and to know the effectiveness the structure of the internal control system on PT. Nicosa Sejahtera, East Lampung. . The research was descriptive-qualitative. Moreover, the instruments in the data collection technique used observation, interviews, and documentation. Furthermore, the data analysis technique started with data reduction, data presentation, and drawing conclusions. Based on the result show that the implementation of internal control within the company has been running as it should, each element of internal control has been running effectively.